(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
Abstract The study aimed to identify the expansion in granting credit to Iraqi banking institutions and its impact on the financial position of Iraqi banks in terms of revenues, profits, expenses and property rights in banks, as the expansion in granting bank credit will correspond to an increase or decrease in some items of the balance sheet and the financial position of banks, so the problem of the current study It will be determined through whether the expansion of granting bank credit will affect the financial position of Iraqi banks or not by studying the selected research community of the 10 Iraqi banks listed in the Iraq Stock Exchange, The research sample included the upper and middle managements in the mentioned Iraqi banks, and they are the financial managers, control managers (audit), credit managers, and investment portfolio managers use spss v26. The results for the study sample of 50, The results of the study showed that the presence of the impact relationship and the positive and strong correlation between the expansion of credit through increasing profits and revenues can contribute to improving the financial position, increasing self-capital, reducing the financial risks of the bank, and increasing the distributions of shareholders and property rights, which will improve the financial position of the bank and enhance its ability to provide services in When reducing expenses, it can improve the performance of the bank, increase profitability, and lead to improving the financial position of the bank. The study reached several recommendations, the most important of which is that banks should work to increase revenues and profits by improving their banking services, developing their financial products, and increasing the attractiveness of their shares by increasing dividends to shareholders, and searching for a way to reduce expenses and improve their efficiency, such as improving their operations. internal and streamlined operations.